2022
DOI: 10.3389/fimmu.2022.841716
|View full text |Cite
|
Sign up to set email alerts
|

HDAC Inhibition as Potential Therapeutic Strategy to Restore the Deregulated Immune Response in Severe COVID-19

Abstract: The COVID-19 pandemic has had a devastating impact worldwide and has been a great challenge for the scientific community. Vaccines against SARS-CoV-2 are now efficiently lessening COVID-19 mortality, although finding a cure for this infection is still a priority. An unbalanced immune response and the uncontrolled release of proinflammatory cytokines are features of COVID-19 pathophysiology and contribute to disease progression and worsening. Histone deacetylases (HDACs) have gained interest in immunology, as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 110 publications
(121 reference statements)
0
20
0
Order By: Relevance
“…46 Recent work by Ripamonti et al established the beneficial use of HDAC6 selective inhibitors in attenuating the dysregulated immune responses seen in severe COVID-19 infections by mitigating the associated cytokine storm responses. 47 These studies attributed these beneficial anti-inflammatory properties to its HDAC6 selectivity. Moreover, the reduced pan-selectivity of SAHA-OH could be linked to its anti-inflammatory properties.…”
Section: ■ Discussionmentioning
confidence: 99%
“…46 Recent work by Ripamonti et al established the beneficial use of HDAC6 selective inhibitors in attenuating the dysregulated immune responses seen in severe COVID-19 infections by mitigating the associated cytokine storm responses. 47 These studies attributed these beneficial anti-inflammatory properties to its HDAC6 selectivity. Moreover, the reduced pan-selectivity of SAHA-OH could be linked to its anti-inflammatory properties.…”
Section: ■ Discussionmentioning
confidence: 99%
“…With respect to tinotamustine, a novel repurposing strategy for COVID-19 emerged recently. The accumulation of highly acetylated histones induced by this drug (and compounds with a similar mode of action) results in induction of chromatin remodeling and modulation of gene expression, which has been shown to reset the deregulated immune reaction observed in severe COVID-19, particularly by lowering the uncontrolled inflammatory response (Ripamonti et al, 2022). Thus, the potential polypharmacological effect of tinotamustine in COVID-19, i.e., amelioration of host's cytokine storm and inhibition of viral MPro, merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…These inhibitors also decrease the activation of monocytes and enhance the differentiation of T cells. A previous study demonstrated the ability of the HDAC inhibitors to hinder IFN-1 expression and downstream effects [ 16 ]. HDAC inhibitors have been found to regulate SARS-CoV-2 entry in epithelial cells by decreasing the expression of angiotensin converting enzyme 2 (ACE2) and blocking ACE2-mediated entry of the virus; consequently, they have been proposed as potential therapeutic agents for COVID-19 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated the ability of the HDAC inhibitors to hinder IFN-1 expression and downstream effects [ 16 ]. HDAC inhibitors have been found to regulate SARS-CoV-2 entry in epithelial cells by decreasing the expression of angiotensin converting enzyme 2 (ACE2) and blocking ACE2-mediated entry of the virus; consequently, they have been proposed as potential therapeutic agents for COVID-19 [ 16 ]. In our study, there was no significant difference in the expression of HDAC2 and HDAC3 between COVID-19 patients and the control group; however, HDAC3 was associated with severity, with lower expression levels correlating with more-severe disease.…”
Section: Discussionmentioning
confidence: 99%